The professoriate: the challenged subject in US higher education. Issue 1 (2nd January 2017) - Stromquist, Nelly P.
ABSTRACT: Developments in the academic world – particularly among research universities – have been pushing US institutions of higher education towards structures and practices that defy the very values of equity and quality they profess to uphold. This is evident in the increasing quantification of scholarly productivity as well as in the growing division of the professoriate into permanent and contingent forms of employment. These two developments feed upon each other to produce a stark differentiation of organisational functions with research separated from teaching, with teaching devalued, and with shared governance a convenient but empty trope. Focusing on the concept of agency, this article describes these developments in detail, and explores the causes of the considerable loss of professional autonomy, as agency is weakly manifested to protect a more sensitive assessment of academic excellence, and even much less to defend the exploited contingent faculty. Exogenous forces have reduced the professoriate's discretionary powers, yet there is still room for action.